A Modified Current-Mode VCSEL Driver for Short-Range LiDAR Sensor Applications in 180 nm CMOS - Juntong Li; Yeojin Chon; Shinhae Choi; Sung-Min Park (Photonics, 2024)
This paper presents a modified current-mode vertical-cavity surface-emitting laser (VCSEL) driver as a transmitter for short-range light detection and ranging (LiDAR) sensors, where a stable bias generator is suggested with a regulated cascode current mirror circuit to provide the bias current of 1 mA with a trivial deviation of 5.4%, even at the worst-case process–voltage–temperature (PVT) variations. Also, a modified current-steering logic circuit is exploited with N-type MOSFET (NMOS) switches to deliver the modulation currents of 0.1~10 mApp to the VCSEL diode simultaneously, with no overshoot distortions. Post-layout simulations of the modified current-mode VCSEL driver (m-CMVD), using 180 nm CMOS technology, demonstrate very large and clean output pulses with significantly reduced signal distortions. Hereby, the VCSEL diode is transformed into an equivalent circuit with a 1.6 V DC voltage and a 50 Ω resistor for circuit simulations. The proposed m-CMVD consumes a maximum of 11 mW from a 3.3 V supply voltage and the chip core occupies an area of 0.196 mm2.